PENGARUH SISTEM INFORMASI SUMBER DAYA MANUSIA,KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI SEKRETARIAT DPRD PROVINSI SUMATERA BARAT - Habibatul Hidayati; Anisa Putri (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine the effect of HR information systems, competence and work discipline on employee performance at the DPRD secretariat of West Sumatra Province, this research is a quantitative study, the sampling method uses total sampling with a total of 60 respondents. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the Human Resources information system has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance, and work discipline has a positive and significant effect on employee performance